Effects of Soymilk and Milk Solid not Fat on Soy Ice Cream Quality - Shrestha, Megha; Maskey, Bunty (Himalayan Journal of Science and Technology, 2018)
Soy ice cream is a vegan friendly frozen dessert prepared using soymilk as the major ingredient. Nine formulations of soy ice cream were prepared with varying levels of soymilk (0-100%) and milk solid not fat (MSNF) (10-12%). From sensory evaluation, 50% soymilk and 12% MSNF resulted the best ice cream of all the formulations. From response study, it was found that the overrun was positively affected but melting rate was negatively affected by soymilk whereas both the overrun and melting rate were negatively affected by MSNF and the formulation of 100% soymilk and 10% MSNF was found to be the best optimized. Chemical analysis of the best product (50% soymilk and 12% MSNF) showed 64% moisture, 10% fat, 5.6% protein, 18.9% total sugar and 0.4% ash. Hence, soy ice cream can be prepared by using milk (50%), soymilk (50%) and MSNF (12%) with physical, chemical and sensory qualities similar to that of plain ice cream.